2003
DOI: 10.1590/s0101-60832003000600004
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba e memória: mito ou realidade?

Abstract: RESUMOO uso dos extratos de Ginkgo biloba para tratamento e prevenção de afecções relacionadas ao envelhecimento e, particularmente, de transtornos da memória baseia-se em práticas médicas ancestrais e estende-se largamente nos dias de hoje. Contudo, a literatura médica carece de estudos sistemáticos sobre a eficácia de seus princípios ativos no tratamento das demências e da doença de Alzheimer. Em virtude do uso muitas vezes indiscriminado desses produtos, além da falta de um controle adequado sobre sua produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
4
0
2
Order By: Relevance
“…In vitro studies have shown three biological benefits of this substance: prevention of neurotoxicity by amyloid beta, the inhibition of apoptotic pathways, and protection from oxidative damage 19 . Nevertheless, previous randomized trials have revealed that long-term use of Ginkgo Biloba extract did not reduce the risk of AD's progression when compared with a placebo 20,21 .…”
mentioning
confidence: 99%
“…In vitro studies have shown three biological benefits of this substance: prevention of neurotoxicity by amyloid beta, the inhibition of apoptotic pathways, and protection from oxidative damage 19 . Nevertheless, previous randomized trials have revealed that long-term use of Ginkgo Biloba extract did not reduce the risk of AD's progression when compared with a placebo 20,21 .…”
mentioning
confidence: 99%
“…It is constituted by 24% of ginkgo flavone glycosides and 6% of terpenoids (FORLENZA, 2003). Ginkgo biloba has antioxidant mechanism of action (MACARENCO et al, 2001) and antiapoptotic activity (FORLENZA, 2003).…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…G. biloba possibly potentiates the effect of acetylcholinesterase (CZAP, 2002). Therefore, it is recommended for clinical treatment of Alzheimer's disease (FORLENZA, 2003), cardiovascular diseases, sexual impotence, hepatic fibrosis, memory improvement, cerebral vascular insufficiency, PMS and some kinds of cancer (CZAP, 2002). In patients administered with anticoagulants, there may be a formation of subdural hematoma (ROSENBLATT & MINDEL, 1997).…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…These effects may lead to the development of several diseases, particularly pathologies related to the central nervous system (Alok et al, 2014;Pereira et al, 2014). Because the EGb 761 extract has known antioxidant activity against oxidative stress, it may be effective in both treatments and prophylaxis of chornic degenerative diseases (Diamond et al, 2000;Puppo and Silva, 2008;Jager et al, 2006;Berigan and Page, 2000;Forlenza, 2003;Gauthier and Schlaefke, 2014;Siegel et al, 2014;Cheng et al, 2015;Montes et al, 2015;Solfrizzi and Panza, 2015).…”
Section: Introductionmentioning
confidence: 99%